Briquette Training on Briquette Making from Coconut Shells: Training on Briquette Making from Coconut Shells - Kurnianingtyas, Chandra Dewi (Jurnal Atma Inovasia, 2023)
Sanggrahan Village, which was determined as the location for the Community Service Program for group 7 (seven), has a lot of natural potential. One of the vast potentials are coconut trees. Briquettes are materials that can be used as fuel to ignite and maintain flame. Coconut shell waste is one of the materials we used as the raw material of our project, which then will be made into briquettes. The making of briquettes from coconut shell waste was carried out on December 28, 2022, at the Sanggrahan Village Hall. Based on the practices in the training work program for making briquettes from coconut shells, the result of the burned briquettes can burn entirely over a long period. The texture of the dough should be smooth and dry because if the dough is too wet, it will be difficult for the briquettes to dry and harden, while a dough that is too dry will make the briquettes hard to intertwine and break easily when hit by a hard object. The effort to develop and manage briquettes that Sanggrahan Village can carry out is marketing the briquettes they have produced with a broader market.